Uso de las curvas de preferencia del macroinvertebrado Chironomidae, alimento base de la especie Eremophilus Mutisii, con el fin de evaluar la aplicabilidad de la metodología IFIM en el cálculo de los caudales ambientales para el río Sisga en el departamento de Cundinamarca (2017)
The development of projects that involve the use of the water resource in Colombia or in the world, requires studies to maintain a minimum level of water that guarantees the adequate development of the species of the rivers. In Colombia, the use of the IFIM methodology in flat rivers has been implemented, which is based on a quantitative relationship between the physical and hydraulic parameters of the habitat and the series of flows, but due to the great biodiversity, it is not possible to generalize the use of this methodology for the country, without carrying out the study in mountain rivers. The present work, seeks to apply the IFIM methodology through modeling using the PHABSIM software, to determine optimal ecological flows in a section of the Sisga River which corresponds to 3.2 km from the discharge of the reservoir that bears its name until the mouth in the Bogotá river, and that by its characteristics can be classified as a mountain river. First of all, the collection of information necessary to carry out the modeling in PHABSIM was carried out. The hydrological and topobatimetric information was provided by the Autonomous Regional Corporation of Cundinamarca, CAR, while the information of suitability curve of the macroinvertebrate Chironomidae, being this the main feeding source of the fish Eremophilus mutisii (captain of the savanna), was obtained from the Work "Habitat Suitability Curves for Bentonic Macroinvertebrates: a Tool for the Estimation of Environmental Flows" by Cardona, (2012), since Colombia has not developed field work for the collection of biological information on fish species . With the necessary information obtained and taking into account that PHABSIM has low processing capacity, 10 different models were carried out, which represent the 10 sections in which the river had to be divided. Finally, it is concluded that the use of the IFIM methodology is of great importance in mountain rivers, since with the help of the PHABSIM program, and taking into account physical and habitat parameters, reliable results can be obtained for decision making.